1996
DOI: 10.1377/hlthaff.15.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Purchasing Strategies On Local Health Care Systems

Abstract: Efforts to control health care costs increasingly rely on purchasers to seek the best value for their investment. In this examination of purchasing strategies in fifteen communities, most purchasers employed traditional strategies to reduce their direct costs, such as shifting costs to employees and switching from indemnity to managed care plans. Fewer purchasers--mostly large companies, public agencies, and coalitions--were using more resource-intensive strategies such as direct contracting with providers or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…45 Large organizations continued to develop on both supply and demand sides of the health insurance and health care delivery markets, and both hierarchically integrated and contractually linked arrangements continued to spread. 46 However, the increase in state authority sought by the Clinton administration (and with it the increase in the proportion of the population with health coverage) was generally not achieved, despite some incremental gains. The most dramatic change in the balance of influence in the U.S. health care arena, rather, was the decline of the influence of the medical profession in the private market-oriented system, and the rise of for-profit private financial interests.…”
Section: H E a L T H A F F A I R S~m A Y / J U N E 1 9 9 9 D Y N A M mentioning
confidence: 99%
“…45 Large organizations continued to develop on both supply and demand sides of the health insurance and health care delivery markets, and both hierarchically integrated and contractually linked arrangements continued to spread. 46 However, the increase in state authority sought by the Clinton administration (and with it the increase in the proportion of the population with health coverage) was generally not achieved, despite some incremental gains. The most dramatic change in the balance of influence in the U.S. health care arena, rather, was the decline of the influence of the medical profession in the private market-oriented system, and the rise of for-profit private financial interests.…”
Section: H E a L T H A F F A I R S~m A Y / J U N E 1 9 9 9 D Y N A M mentioning
confidence: 99%
“…However, as other studies have, our study found that only a few corporations were conducting significant quality-oriented activities. 11 These companies have worked individually and collaboratively with health plans to produce information to support the assessment of quality of care. Some have begun to consider quality in their purchasing decisions.…”
Section: How Companies Implemented Value Purchasingmentioning
confidence: 99%
“…Although some PPOs have attempted to build in innovations that are associated with health maintenance organizations In addition, to attract the self-insured market, even health plans with integrated delivery systems, such as Kaiser Permanente, are learning how to bill third-party administrators for ERISA plans on a fee-for-service basis. 5 Thus, at the same time that traditional fee-for-service providers are being asked to assume financial risk, organizations steeped in cultures of costeffectiveness are being given incentives to regress to cost-based reimbursement.…”
Section: Bob Berenson a Physician Is Cofounder And Codirector Of Thmentioning
confidence: 99%